(untitled) (Pulse, 2015)
A 30 year old man admitted with the complaints of generalized convulsions, headache and amnesia. The radiological and neuro-pathological findings were interhemispheric epidermoid tumor, which is a rare location. The tumor was removed completely. The diagnosis and management of epidermoid tumors are discussed by reviewing the literature. Pulse Vol.7 January-December 2014 p.46-49